Financial innovations Involving the Greek Drachma - Gatzonas, E. (IMF Working Papers; Working Paper ;, 1997)
During the last decade, a number of new financial instruments and derivative products related to the Greek drachma have emerged in local as well as international capital markets. The paper analyzes the characteristics of these financial instruments which are traded in organized exchanges and over-the-counter (OTC) markets, and evaluates the conditions under which they have evolved. Drawing from legislative and industry developments in the European Union (EU) and the United States, the paper also examines the effects and implications of such developments for local markets and for the conduct of monetary and foreign exchange policies and argues for the need for sound macroeconomic policies.